(untitled) (Third Sector Social Economic Review, 2021)
The Tanzimat period, which formed the basis of the modernization stages for the Ottoman Empire, witnessed important changes and transformations. New institutions were also needed as a result of the idea of benefiting from Europe’s mentality with the reforms that were put forward in this period and implemented in order to prevent the collapse of the state. With these regulations under the name of restructuring, the change of the social order has also been directed, and this period has become a process bearing the traces of many changes in legal, administrative, social and economic terms. With the Tanzimat, the effects of the changes experienced in every field have also been reflected in the changes in educational institutions and the judicial order, in parallel with this, legalization studies have enabled new organized institutions to be put into practice. In this study, the regulations in the context of the developments of the Tanzimat period were examined and the some new institutions that have gone into action in this period are discussed.